PRE-EVALUASI GERAKAN ONE DAY NO RICE (ODNR) DITINJAU DARI KEANEKARAGAMAN KONSUMSI PANGAN PEGAWAI DI KANTOR PEMERINTAH KOTA DEPOK - Astuti, Trina; Christine, Dhea (GIZI INDONESIA, 2016)
The aim of the study is to evaluate "One Day No Rice (ODNR) movement" based on food diversification consumption of government employee in Depok. The study design was descriptive analytic survey. Samples of 74 people were  taken through purposive sampling. The inclusion criteria covered employee of Depok City Government,  staffing level of II and III, worked at least 3 years, and healthy. Samples that have a history of diabetes mellitus were excluded.The results showed that of 68.9 per cent were aged less than 40 years; 58.1 per cent of men; 45.9 per cent had a degree of S1 or equivalent; 66.2 per cent with staffing  level of III.  Amounted to 90.5 per cent employees informed about ODNR movement, but only 5.4 per cent have applied food diversification consumption. Fisher Exact test showed no relationship between application food diversification consumption among employees with age (p = 0.651), gender (p = 0.107), education level (p = 0.275), staffing level (p=0,584) and knowledge on ODNR movement (p = 1.000). Considering the importance of food diversification, it is recommended to continue the movement with strengthened strategy on health promotion.  Promotion with leaflets and brochures as well as nutrition balanced education associated with ODNR to prevent non-communicable diseases such as diabetes mellitus, obesity, and overweight caused by undiversified food consumption.